Dampak Stres Kerja dan Rotasi Kerja Terhadap Organizational Citizenship Behaviour Pada Bank Syariah Indonesia Surakarta - Chandra Wisnu Utomo (Universitas Muhammadiyah Magelang, 2021)
At Bank Syariah Indonesia Surakarta, the purpose of this study is to investigate and assess the impact of work stress and job rotation on organizational behavior. This is a quantitative study that takes a case study approach in the field. The basic data used in the search was derived from the responses of the respondents. Meanwhile, secondary data is gathered from corporate profiles and human resources literature. Workplace stress has an impact on organizational citizenship behavior, and job rotation has an impact on organizational citizenship behavior, according to the findings of this study.